An introduction to the philosophy of mind - Lowe, E. J. (Cambridge University Press, 2000)
In this book Jonathan Lowe offers a lucid and wide-ranging introduction to the philosophy of mind. Using a problem-centred approach designed to stimulate as well as instruct, he begins with a general examination of the mind-body problem and moves on to detailed examination of more specific philosophical issues concerning sensation, perception, thought and language, rationality, artificial intelligence, action, personal identity and self-knowledge. His discussion is notably broad in scope, and distinctive in giving equal attention to deep metaphysical questions concerning the mind and to the discoveries and theories of modern scientific psychology. It will be of interest to any reader with a basic grounding in modern philosophy.